2018
DOI: 10.1016/j.bpj.2017.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphorylation in Moesin Interactions with PIP2-Containing Biomimetic Membranes

Abstract: Moesin, a protein of the ezrin, radixin, and moesin family, which links the plasma membrane to the cytoskeleton, is involved in multiple physiological and pathological processes, including viral budding and infection. Its interaction with the plasma membrane occurs via a key phosphoinositide, the phosphatidyl(4,5)inositol-bisphosphate (PIP), and phosphorylation of residue T558, which has been shown to contribute, in cellulo, to a conformationally open protein. We study the impact of a double phosphomimetic mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…However, these results provide no understanding of their subcellular localisation during TEM. Numerous studies have shown that PIP 2 binding of moesin precedes phosphorylation of ERM proteins ( Ben-Aissa et al, 2012 ; Lubart et al, 2018 ). To address the impact of PIP 2 binding on moesin activation during TEM, a series of lysine (K) to asparagine (N) mutations at positions 253, 254, 262 and 263 (K253N, K254N, K262N and K263N), which are known to be important for PIP 2 binding ( Barret et al, 2000 ), were engineered into the moesin–GFP FERM domain (denoted 4N) and stably reconstituted into cells lacking endogenous moesin.…”
Section: Resultsmentioning
confidence: 99%
“…However, these results provide no understanding of their subcellular localisation during TEM. Numerous studies have shown that PIP 2 binding of moesin precedes phosphorylation of ERM proteins ( Ben-Aissa et al, 2012 ; Lubart et al, 2018 ). To address the impact of PIP 2 binding on moesin activation during TEM, a series of lysine (K) to asparagine (N) mutations at positions 253, 254, 262 and 263 (K253N, K254N, K262N and K263N), which are known to be important for PIP 2 binding ( Barret et al, 2000 ), were engineered into the moesin–GFP FERM domain (denoted 4N) and stably reconstituted into cells lacking endogenous moesin.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Förster Resonance Energy Transfer (FRET) and co-immunoprecipitation experiments have shown that ezrin oligomers form in cells [77,90], and dimeric ezrin has been purified from placental tissue [91,92]. The interaction of the FERM and CTD is strong with little exchange between monomers and dimers occurring [92,93,94,95]. Small-angle X-ray scattering (SAXS) studies of purified ezrin dimer have shown that it largely adopts a domain-swapped dumbbell structure (Figure 4b) [56].…”
Section: Merlin-erm Structurementioning
confidence: 99%
“…The linkage between the cortex and the membrane is thus realized by linker proteins, for example, the ERM proteins Ezrin, Radixin, and Moesin (24,25), which can simultaneously bind to the membrane and the actin filaments. The mechanism of this binding is rather complex and depends on posttranslational alterations of the binding protein (26,27) as well as the composition of the membrane (28)(29)(30)(31). Divalent ions are ubiquitous in cells.…”
mentioning
confidence: 99%